Epidemiology of major depressive disorder in mainland china: a systematic review. - Lian Gu; Juanjuan Xie; Jianxiong Long; Qing Chen; Qiang Chen; Runde Pan; Yan Yan; Guangliang Wu; Baoyun Liang; Jinjing Tan; Xinfeng Xie; Bo Wei; et al. (PLoS ONE)
Background Major depressive disorder (MDD) is one of the important causes of disease burden in the general population. Given the experiencing rapid economic and social changes since the early 1990s and the internationally recognized diagnostic criteria and interview instruments across the surveys during 2001-2010 in china, the epidemiological studies on MDD got varied results. We performed this meta-analysis to investigate current, 12-month and lifetime prevalence rates of MDD in mainland China. Methods PubMed, Embase, Chinese Biological Medical Literature database (CBM), Chinese National Knowledge Infrastructure database (CNKI), and the Chinese Wanfang and Chongqing VIP database were searched for associated studies. We estimated the overall prevalence of MDD using meta-analysis. Conclusions Seventeen eligible studies were included. Our study showed that the overall estimation of current, 12-month and lifetime prevalence of MDD was 1.6, 2.3, 3.3%, respectively. The current prevalence was 2.0 and 1.7% in rural and urban areas, respectively; between female and male, it was 2.1 and 1.3%, respectively. In addition, the current prevalence of MDD diagnosed with SCID (Structured Clinical Interview for DSM-IV) was 1.8% and that diagnosed with CIDI (Composite International Diagnostic Interview) was 1.1%. In conclusion, our study revealed a relatively high prevalence rate in the lifetime prevalence of MDD. For current prevalence, MDD diagnosed with SCID had a higher prevalence rate than with CIDI; males showed a lower rate than females, rural residents seemed to have a greater risk of MDD than urban residents.